2012
DOI: 10.1080/10410236.2011.578333
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Physicians' Attitudes Toward Sharing Information With Patients and Addressing Psychosocial Needs: A Cross-Sectional Study in Greece

Abstract: Sharing information with patients and addressing their psychosocial needs are recognized as fundamental practices of patient-centered physicians. Our study explored predictors of physicians' patient-centered attitudes and yielded a better understanding of the relative influences of job satisfaction, employment status, specialty, previous communication skills training, and sociodemographic factors. Physicians who participated in 13 identical workshops offered throughout Greece were invited to complete a battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Female medical practitioners and students tend to report greater preference for patient-centredness than their male counterparts (Haidet et al, 2002;Krupat et al, 2000;Wahlqvist et al, 2010). Cultural, socio-economic, and religious background can also explain preferences for patient-centredness among medical practitioners and students (Haidet et al, 2002;Tsimtsiou et al, 2012). Further, experienced medical practitioners show greater patient-centred behaviours than their less experienced peers (Krupat et al, 2000;Wahlqvist et al, …”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Female medical practitioners and students tend to report greater preference for patient-centredness than their male counterparts (Haidet et al, 2002;Krupat et al, 2000;Wahlqvist et al, 2010). Cultural, socio-economic, and religious background can also explain preferences for patient-centredness among medical practitioners and students (Haidet et al, 2002;Tsimtsiou et al, 2012). Further, experienced medical practitioners show greater patient-centred behaviours than their less experienced peers (Krupat et al, 2000;Wahlqvist et al, …”
mentioning
confidence: 82%
“…Practitioners from some medical specialities also have greater preferences for patient-centredness than others (Chan & Ahmad, 2011). Further, medical practitioners trained in communication skills show greater preferences for patient-centredness than their peers who have not received such training (Tsimtsiou et al, 2012).…”
Section: Original Articlementioning
confidence: 98%
See 2 more Smart Citations
“…Although better health status has been associated in outpatients with increased need for sharing information and power with the physician [5,7,11], an American study in hospitalized patients demonstrated that better health was associated with their preference to have the physician make their treatment decisions [6], possibly reflecting the influence of different health care contexts and type of decisions that have to be made. Moreover, although an association between the strength of religious beliefs and patient-centered attitudes has been previously described in Greek medical students and physicians, the effect of religious beliefs is an understudied parameter in patients' attitudes [6]; more specifically, there has been described a negative influence on students' attitudes toward sharing information and a positive influence on physicians' psychosocial orientation [12,13]. Furthermore, in primary care settings, psychological co-morbidity was found to have an impact on patients' preferences for shared decision-making [8], while low perceived social support was associated with problematic resident-patient relationships [14].…”
Section: Introductionmentioning
confidence: 96%